Fucoidan functionalization on poly(vinyl alcohol) hydrogels for improved endothelialization and hemocompatibility. (August 2020) - Yao, Yuan; Zaw, Aung Moe; Anderson, Deirdre E.J.; Hinds, Monica T.; Yim, Evelyn K.F.
Abstract: The performance of clinical synthetic small diameter vascular grafts remains disappointing due to the fast occlusion caused by thrombosis and intimal hyperplasia formation. Poly(vinyl alcohol) (PVA) hydrogels have tunable mechanical properties and a low thrombogenic surface, which suggests its potential value as a small diameter vascular graft material. However, PVA does not support cell adhesion and thus requires surface modification to encourage endothelialization. This study presents a modification of PVA with fucoidan. Fucoidan is a sulfated polysaccharide with anticoagulant and antithrombotic properties, which was shown to potentially increase endothelial cell adhesion and proliferation. By mixing fucoidan with PVA and co-crosslinked by sodium trimetaphosphate (STMP), the modification was achieved without sacrificing mechanical properties. Endothelial cell adhesion and monolayer function were significantly enhanced by the fucoidan modification. In vitro and ex-vivo studies showed low platelet adhesion and activation and decreased thrombin generation with fucoidan modified PVA. The modification proved to be compatible with gamma sterilization. In vivo evaluation of fucoidan modified PVA grafts in rabbits exhibited increased patency rate, endothelialization, and reduced intimal hyperplasia formation. The fucoidan modification presented here benefited the development of PVA vascular grafts and can be adapted to other blood contacting surfaces.